Perbandingan Karakteristik Berkala Ilmu Perpustakaan dan Informasi dengan Jurnal Kajian Informasi dan Perpustakaan Periode 2018-2020 - suhendani suhendani; Rochani Nani Rahayu (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Comparison of the characteristics of the Library and Information Science Periodic (BIPI) and the Journal of Information and Library Studies (JKIP) 2018-2020, was carried out using the bibliometric analysis method. The research objectives are to find out: a) Number of articles published during 2018-2020; b) Journal authorship pattern; c) Degree of collaboration; d) The most prolific writer; e) The most productive universities; f) The most productive agencies/institutions; f) The most productive city; g) Most research topics based on author's keywords. The results showed that the articles published by BIPI and JKIP were 60, and 42 titles respectively and the number of authors were 114 people (65 males; and 49 females) and 78 respectively. people (41 males and 37 females). BIPI's degree of collaboration is 0.75, and JKIP's is 0.66. N.A. Damayani emerged as the most prolific writer in both BIPI and JKIP, with the number of articles written in 3 titles in BIPI, and 2 titles in JKIP. Gadjah Mada University is in the first position to appear in BIPI, and Padjadjaran University is the largest university for JKIP. Yogyakarta is the most populous city in BIPI, and Bandung is the largest city for JKIP. Canberra is the only contributor from abroad. The most keywords in BIPI are quality and Rare newspapers are the most keywords in JKIP. The conclusion of the study is that the number of BIPI articles is higher than that of JKIP, that there are more collaborations of writers in BIPI than JKIP, and there are more male authors than female authors, both at BIPI and JKIP. The universities where the journals are published contribute the most, both at BIPI and JKIP. Most keywords are quality for BIPI, and rare newspaper for JKIP.